Historical cut of natural geographical research formation in Kharkiv society of naturalists in the second half of XIX – early XX century - Половка, C. Г.; Половка, О. А. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
Problem Statement and Purpose. The aim of the article is, in the historical screening cut of scientific and social activities in the field of natural geography in the society of scientists in the first university on the territory of Ukraine (the second half of XIX – early XX century).Data & Methods. Research data were collected from libraries of I. I. Mechnikov Odessa National university and P.Tychyna UGPU, and these were the main sources of information. Scientific works (monographs, encyclopedias, articles and electronic resources at various levels) by the famous Russian scientists, scientists from the former Soviet Union and Ukraine (1906–2014) were alo widely used. In writing this research, we used methods of retrospective studies, historical, geographical and scientific methods of analysis to summarize the processed materials.Results. A retrospective analysis of a large number of materials, has led us to the main results of our research.It was found out that the formation of natural geography of Ukraine was attended by experts from different fields of knowledge.As a result, the research has confirmed that:1. Naturalists of Kharkiv Society have played a leading role in the formation and development of the natural geographical area of expertise in Slobozhanschyna at Kharkiv University, where geography as an academic discipline was introduced in 1889 thanks to the activity of members of the public association.2. Science in the process of its development is based on its respective fields. At their intersection there are new research areas and «young» science, like bio-geographical areas of natural geography and ecology, which are now being intensively developed and enrich researchers with new knowledge about the nature of the Earth.